تحليل بعض مؤشرات الأداء في قطاع خدمة الهاتف النقال في الجزائر - واضح، فواز; مرغاد، لخضر (جامعة غرداية, 2015)
تناولت هذه الدراسة موضوع الأداء في قطاع خدمة الهاتف النقال في الجزائر الذي يعد جانباً مهماً من جوانب اهتمام كبرى المؤسسات الاقتصادية، ومفتاح النجاح بالنسبة لأي مؤسسة مهما كان نوعها وهدفها وقد ركزنا في دراستنا هذه على الأداء الكلي على مستوى القطاع ككل نظراً لأهميته في تكوين نظرة دقيقة على جاذبية أي صناعة، وكذلك تأثره بكل من هيكل الصناعة والاستراتيجيات المعتمدة من طرف المؤسسات العاملة في القطاع، كما ركزنا على ثلاثة مؤشرات مهمة للحكم على مستوى الأداء وهي (الربحية، النمو في بعض المؤشرات الاقتصادية، التقدم التقني)، وخلصت الدراسة إلى وجود نمو سريع في بعض المؤشرات الاقتصادية مثل الحصة السوقية ورقم الأعمال، إضافة إلى تسجيل معدلات ربحية متزايدة، كما وقفنا على مستوى التكنولوجيا المستخدمة في القطاع والتي لم ترق بعد إلى تطلعات الزبائن خاصة ما تعلق بالخدمات المقدمة للمؤسسات ورجال الأعمال، لكن وبالرغم من ذلك فإن المؤشرات السالفة الذكر تعتبر حافزاً كبيراً للمؤسسات الراغبة في الاستثمار في هذه الصناعة على غرار أورانج وفودافون.
This study deals with the subject of performance in the market of mobile telephony in Algeria. Indeed, the latter is a component of great interest for large economic enterprises and one of the key factors that determine their success. We focused in this study on the overall performance of the mobile industry saw its leading role as one of the prerequisites for each industry and its impact on industrial structure and strategies adopted by companies belonging to the sector. To evaluate performance, we opted for the choice of the three following indicators: profitability, the growth of certain economic indicators and technical progress. At the end of our study, it was observed a rapid growth in some economic indicators such as market share and turnover, as well as constantly growing profitability rate. We also noted the low level of technology in this sector and which does not meet the expectations of customers in particular with regard to services provided to businesses and businessmen. Despite the current situation of the sector, the indicators mentioned above constitute factors of attraction for companies that want to invest in this industry like Orange and Vodafone.
Keywords: المؤسسات العامة -- قطاع الاتصالات -- الأسواق المحلية -- الميزة التنافسية -- الجزائر